Vaginal progesterone as luteal phase support in natural cycle frozen-thawed embryo transfer (ProFET): protocol for a multicentre, open-label, randomised controlled trial - Kenny A Rodriguez-Wallberg; Christina Bergh; Ali Khatibi; Annika Strandell; Mats Brännström; Caroline Stadelmann; Kristbjörg Heiður Olsen; Margareta Kitlinski; Susanne Liffner; Eva Lundborg; Göran Westlander; Gabriella Widlund; et al. (BMJ Open)
Introduction Vaginal progesterone supplementation is frequently given to patients receiving frozen embryo transfer (FET) in the natural cycle aiming to increase the chance of pregnancy and live birth. To date, only a few studies have investigated if progesterone supplementation is beneficial in these cycles and the level of evidence for progesterone supplementation is very low.Methods and analysis The ProFET trial is a multicentre, open-label, randomised controlled trial powered for this investigation, including 1800 women with regular menstrual cycles (24–35 days), aged 18–43 years planned for natural cycle-FET receiving a single blastocyst for transfer. Participants are randomised (1:1:1) to either luteal phase progesterone for 3 weeks, luteal phase progesterone for 7 weeks or no luteal phase progesterone. The participating study centres consist of 12 in vitro fertilisation-clinics in Sweden and 1 in Iceland. The primary outcome is to investigate if luteal phase support (LPS) by vaginal progesterone increases the chance of a live birth per randomised patient in a natural FET cycle compared with no LPS.Ethics and dissemination The trial was approved by the Swedish Ethical Review Authority (ID 2020-06774, 2021-02822 and 2022-01502-02) and the Swedish Medical Products Agency (ID nr 5.1-2020-102613). All participants are required to provide written informed consent. The outcome of this study will be disseminated to the public through broadcasts, newspapers and presentations at scientific congresses as well as publications in international scientific journals.Trial registration number NCT04725864.